A feasibility study on operating a fish feed mill in Minalin, Pampanga - Butacan, Lorelie Sophia; Galicia, Carlo; Laforteza, Trojan; Marasigan, Emmanuell (Quezon City College of Engineering, University of the Philippines Diliman, 2009)
The Chief Executive Officer of AL-LY Merchandising Company Mr. Alberto M. Magpayo has started his long-term plan of putting up a feed mill business. The company is a mass producer and distributor of aquaculture fish that are delivered throughout Regions 1,3,and 4. This study covered the evaluation of the feasibility of setting up a fish feed mill in Minalin, Pampanga that would provide the demands primarily of AL-LY Merch. Co., their business partners, their direct clients and other fish pond owners in Pampanga to replace the costly purchasing of commercial fish feeds. The planned manufacturing company was named AMMCO Fish Feeds Milling Company. In order to fulfill the needs of AL-LY Merch. Co. and company, the planned feed mill must produce four different types of feeds namely frymash which is in mashed form, and starter, grower, and finisher that are in pellet form. The different types of feeds correspond to the different phases of the fish's life cycle. Frymash are for fingerlings, starter pellets are for young adults, grower pellets are for adults, and finisher pellets are fed to fishes that are soon to be harvested. A wide range of variables related to market technical, socio-profitability, organization & management, and financial feasibility are considered, including: demand-supply analysis, market potential, material requirements evaluation, capacity and production planning, facilities and design, operating and capital cost projections, financial statements and investment proposals, organizational structure, and social benefits assessment. The market analysis resulted in a positive potential market based on the findings of the existence of demands unsatisfied by Region 3 feed millers. Pampanga being top four of the Philippine aquaculture producing provinces and the only province included from the region, the supply of fish feeds from Region 3 producers is concentrated to it. A 5-year fish feed demand projection of Pampanga was established through relating aquaculture fish production historical data that was provided by the Bureau of Agricultural Statistics. This projection showed a consistent linear increase in demand from 2009 to 2014 ad was compared to the results of the supply analysis. The evaluation showed that the capacity of the existing 26 feed millers based in Region 3 can only fulfill 47% of Pampanga fish farms' demands. The remaining 53% demand is supplied by feeds producers from the distant provinces of Region 1, Region 2, and NCR. This unsatisfied demand is considered to be AMMCO's potential market, taking over the distant competitors' market share through relatively low market price which is mainly due to geographical advantage, that is, the transportation costs incurred by the company is significantly lower than the far-away competitors.A target market share of 0.5% was established and a 5-year sales forecast was projected based on it. The study concluded that the production of fish feeds is feasible in terms of market potential. After a feasible market was realized, a technical feasibility study was conducted in order to identify whether the product could be produced at the highest possible quality level with minimum cost. The technical study considered the necessary factors for evaluation, including: comprehensive description of the physical and chemical composition of the fish feeds, detailed documentation of the manufacturing processes involved and evaluation of alternative procedures, identification of raw materials, equipment, and tooling that are required, capacity and production planning, facilities design and labor requirements, and cost projections. Since there are no existing standard formulations for fish feeds and company formulas are top secret, a product-mix linear programming model was constructed to identify the optimal mix of raw materials to be used for the formulation. This was done using the proximity analyses provided by the Division of Animal Feeds of the Bureau of Animal Industry as coefficients of variables and the standards for fish feeds nutrient contents provided by the Standards Division of the Bureau of Agricultural Research as the constraints with an objective function of minimizing the total cost of raw materials. Though the resulting mix of ingredients followed the standards for fish feed nutrient contents, it is still subject to scientific tests to make certain that the formulation does conform to the standards and ensure that it is safe for aquaculture feeding. Other essential requirements for production such as land, machinery, material handling tools, laborers, and utilities were determined to be available here and abroad. The cost analysis for the project consisting of fixed investments, pre-operating expenses, working capital, and costs related to forming a company totaled to an amount of Php 340,595,297.10. The study concluded that the construction of the feed mill is technically feasible. Building a new feed mill requires a considerable amount of financial input and so a financial analysis was done to determine if the project is a profitable venture or not. Three financial statements namely income statement, statement of cash flows, and balance sheets were made for the beginning five years of the feed mill operation. The data inputted for these financial statements came from the sales-revenue projection, marketing budget, and cost projections that came from the market and technical studies. Results of the financial statements turned out positive and were further checked through economics discounted cash flow methods namely Net Present Value, Internal Rate of Return, and Payback Period. The calculated NPV for the 5-year operation was PhP 38,686,590.03, hence, the venture is desirable. The calculated Internal Rate of Return for the 5-year operation was 39% and the set Minimum Attractive Rate of Return was 20%, hence, the project is an acceptable and a desirable venture. The payback period was also computed and it showed that in a span of four years of operations, the capital investment for the project has fully been recovered. Therefore, the operation of a feed mill in Minalin, Pampanga is financially feasible. The corporation type of ownership best suited the planned feed mill because the investment for such a business is a very high amount. With a corporation, loans can be more easily done as compared to sole proprietorship or partnership. The separation of the company from its owners as a legal entity is also a very favorable characteristic for the planned business. As for the social-profitability, there are several positive impacts to the communities and even to our country if the feed mill was built. Some of the positive effects are many job openings, increase in gross investment, increase in private spending, and opens business opportunities on the periphery of the plant. Therefore, in terms of social-profitability the project is feasible. The feasibility study of operating a fish feed mill in Minalin, Pampanga resulted in a conclusion that the project is feasible in terms of market, technical, financial, and social profitability aspects.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Feed mills -- Philippines -- Pampanga; Feasibility studies